EVALUATION OF THERAPEUTIC POTENTIAL OF PICRORHIZA KURROA GLYCOSIDAL EXTRACT AGAINST NIMESULIDE NEPHROTOXICITY: A PILOT STUDY - Siddiqi, Afsheen; Alam, Saadia Shahzad; Begum, Sajada; Nazneen, Zainab; Aaqil, Bushra (Journal of Ayub Medical College Abbottabad, 2015)
Background: Picrorhiza kurroa (Pk) is a traditional Ayurvedic herb famous as a potent hepatoprotective agent, only few studies are available on the nephroprotective activity of this herb. The objective of this pilot study was to determine the therapeutic effectiveness of Pk against nimesulide induced toxicity. Methods: This laboratory based experimental study was conducted on mice at National Institute of Health, Islamabad from Dec 2012 to Jan 2013. The mice were divided in to 4 groups. One group was given only PK while the other three groups were given nimesulide in a dosage of 750 mg/kg body weight for 3 days to induce nephrotoxicity and protective effect of Pk was noted by giving 250 mg/kg and 500 mg/kg pk for 14 days to the two of the nimesulide induced nephrotoxicity groups. Biochemical assessment of kidney was done by measuring serum urea & creatinine. Also histology was done to confirm the findings of biochemical assessment. Results: In our pilot study out of 20 mice, 19 mice survived. Only 1 mouse of nimesulide group died. Mean serum urea of nimesulide group was 60 mg/dl and was decreased to 23 mg/dl and 25 mg/dl by two doses of Pk. Mean creatinine in group 2 was 0.55 mg/dl and was decreased to 0.21 and 0.19 mg/dl by two doses of Pk. Conclusion: Our study shows that nimesulide is a potential nephrotoxic drug and its toxic effects on kidney can be minimized by using glycosidal extract of Pk. Keywords: Nimesulide, Picrorhiza kurroa Pk, nephrotoxicity